EMPATHY AND VICARIOUSNESS OF AUTOBIOGRAPHICAL MEMORIES IN THE CHINESE SAMPLE - Gofman, A.A. (Modern Psychology, 2019)
There is empirical evidence suggesting that autobiographical memories of similar experiences evoke empathy [1, 6]. The positive correlation between trait empathy and phenomenology of autobiographical memories was also demonstrated [9]. We assumed that not all autobiographical memories are relevant to empathic feeling. The most promising candidate for scaffolding impact onto empathy, in our point of view, is a specific type of memories – vicarious memories. 96 Chinese participants filled out an Interpersonal Reactivity Index questionnaire and drew their lifelines of the most important events from their childhood in correlation in the timeline. Lifelines were analyzed in regard to the proportion of other-focused and vicarious memories and their emotional valence. The study suggests that the significant predictor of empathy is the distinctive type of childhood memories with specific level of vicariousness. The main focus in these autobiographical memories is shifted to the other person who is active toward the participant.